Modularity and Innovation in Complex Systems - Ethiraj, Sendil K.; Levinthal, Daniel (Management Science, 2004)
The problem of designing, coordinating, and managing complex systems has been central to the management and organization literature. Recent writings have tended to offer modularity as at least a partial solution to this design problem. However, little attention has been paid to the problem of identifying what constitutes an appropriate modularization of a complex system. We develop a formal simulation model that allows us to carefully examine the dynamics of innovation and performance in complex systems. The model points to the trade-off between the destabilizing effects of overly refined modularization and the modest levels of search and a premature fixation on inferior designs that can result from excessive levels of integration. The analysis highlights an asymmetry in this trade-off, with excessively refined modules leading to cycling behavior and a lack of performance improvement. We discuss the implications of these arguments for product and organization design.